2018
DOI: 10.3390/ijerph15122731
|View full text |Cite
|
Sign up to set email alerts
|

Older Worker Identity and Job Performance: The Moderator Role of Subjective Age and Self-Efficacy

Abstract: Older Worker Identity consists of the internalization of negative beliefs and attitudes towards aged employees by these same people. This research aims to explore the moderator role both of subjective age and self-efficacy in the relationship between older worker identity and job performance. The study was conducted with a panel design, including a sample of +40 Spanish workers (n = 200), with two waves (4-months interval). The findings supported the moderator role of subjective age in the relationship, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Additionally, empirical studies have documented that feeling younger than one’s chronological age is associated with greater life satisfaction ( Wurm et al, 2008 ), longer lives ( Kleinspehn-Ammerlahn et al, 2008 ; Levy, Slade, Kunkel, & et al, 2002 ), better overall health ( Levy, Slade, & Kasl, 2002 ), and improved physical abilities ( Stephan et al, 2013 ). In the workplace context, younger subjective age is associated with increases in productivity ( Kunze et al, 2015 ; Rodríguez-Cifuentes et al, 2018 ), adaptability to new work situations ( Rudolph & Baltes, 2017 ), perceived control and motivation ( Shane et al, 2019 ), job crafting ( Nagy et al, 2019 ), and the probability of starting new ventures ( Kautonen et al, 2014 , 2015 ). In addition, Gielnik et al (2018) found that a longer perceived remaining work-life is positively related to entrepreneurial intentions.…”
Section: Baseline Hypothesis: the Covid-19 Pandemic Has A Negative Effect On The Well-being Of Entrepreneursmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, empirical studies have documented that feeling younger than one’s chronological age is associated with greater life satisfaction ( Wurm et al, 2008 ), longer lives ( Kleinspehn-Ammerlahn et al, 2008 ; Levy, Slade, Kunkel, & et al, 2002 ), better overall health ( Levy, Slade, & Kasl, 2002 ), and improved physical abilities ( Stephan et al, 2013 ). In the workplace context, younger subjective age is associated with increases in productivity ( Kunze et al, 2015 ; Rodríguez-Cifuentes et al, 2018 ), adaptability to new work situations ( Rudolph & Baltes, 2017 ), perceived control and motivation ( Shane et al, 2019 ), job crafting ( Nagy et al, 2019 ), and the probability of starting new ventures ( Kautonen et al, 2014 , 2015 ). In addition, Gielnik et al (2018) found that a longer perceived remaining work-life is positively related to entrepreneurial intentions.…”
Section: Baseline Hypothesis: the Covid-19 Pandemic Has A Negative Effect On The Well-being Of Entrepreneursmentioning
confidence: 99%
“…Several studies use various categorizations rather than continuous measures of subjective age (c.f. Boehmer (2007) ; Infurna et al (2010) ; Nagy et al (2019) ; Rodríguez-Cifuentes et al (2018) ). Using a binary measure of subjective age has several advantages.…”
Section: Empirical Analysismentioning
confidence: 99%
“…In order for academic staff to deliver on their academic roles of teaching, research and community engagement, their perception of the levels of ability is paramount. Drawing for the social cognitive theory, self-efficacy enables individuals to persevere and expend efforts towards an end goal amid adversities (Rodr ıguez-Cifuentes et al, 2018). Specifically, individuals with high self-efficacy exhibit sense of competence, intrinsically motivated and actively engaged in their work, resilient and persistent in the face of challenges and setbacks that increases on their positive outlook (commitment) towards the employing institution (Demir, 2020;Hameli and Ordun, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Based on social cognitive theory, self-efficacy provides reasons to rationalise certain acts, thoughts and behaviours (Demir, 2020(Demir, , 2021. As such, it plays a crucial role in explaining why and how individuals engage in certain acts or behaviours, expend effort and persevere to reach an ultimate goal (Rodr ıguez-Cifuentes et al, 2018). Given that OC and organisational commitment depend on individual perceptions and expectations, enhancing high levels of self-efficacy can reduce low levels of culture and commitment (Soomro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is particularly relevant for the master narrative of older employees. The workplace changes that older employees experience affect their selfperceptions and identities (Rodriguez-Cifuentes et al, 2018). Both current societal changes and current workplace changes dissolve old structures.…”
Section: Introductionmentioning
confidence: 99%